STUDI TENTANG TOKOH LORD VOLDEMORT DALAM NOVEL HARRY POTTER AND THE HALF-BLOOD PRINCE KARYA J.K. ROWLING: Sebuah Pendekatan Psikologi Individual - Musarofah, Ulinu Hayil (LANTERN (Journal on English Language, Culture and Literature), 2012)
Harry Potter and The Half-Blood Prince is a novel written by J.K. Rowling in 2005. The purpose of research is to discuss Lord Voldemort’s character through individual psychology theory by Alfred Adler. In order to collect the data, the writer uses library research method that uses many books or sources as the reference to support the analysis. The writer also uses exponential and psychological approaches. Exponential is used to analyze the intrinsic element of the novel. Meanwhile, the individual psychology theory is used to analyze the extrinsic element of the novel. The individual psychology theory consists of striving for superiority, subjective perception, unity of personality, social interest, style of life, and self creative power. The findings of the research include the psychological problem of Lord Voldemort’s character which is called superiority complex. Each individual needs to be superior in his/her environment, but it is his/her decision to develop the superiority into positive or negative superior. In Harry Potter and The Half-Blood Prince, Lord Voldemort’s character shows that he develops his superiority into negative superiority; that is why it can be stated that he has a psychological problem called superiority complex.